DE CONSOLATIONAE PHILOSOPHIAE: KEBAHAGIAAN SEJATI DITEMUKAN DALAM TUHAN (Sebuah Kritik Filosofis Berdasarkan Pemikiran Boethius Terhadap Korban Penipuan Berkedok Trading Binnary Option) - Gerwin Bernardus Putra (Aggiornamento, 2022)
The focus of this paper is a philosophical critique of the mistakes of some Indonesian people in interpreting true happiness based on the thoughts of Boethius in his famous work, De Consolationae Philosophiae. The problem of true happiness has always been a conversation for humans. However, in the early Middle Ages, the problem of true happiness was discovered and analyzed in terms of the highest good, one of which was by Boethius. The purpose of this paper is to find the deepest meaning of true happiness based on the thoughts of Boethius in De Consolationae Philosophiae. The method used is the philosophical elaboration of Boethius' thoughts on true happiness regarding the fraud case by Indra Kenz and Doni Salmanan which has recently been widely reported in the mass media. The Fraud case by Indra Kenz and Doni Salmanan is an example that some Indonesians who are victims of fraud still depend for their happiness on something temporary, namely wealth and popularity. True happiness does not lie in it all. Boethius revealed that true happiness lies in the Supreme Good, namely God.